1992
DOI: 10.1038/bjc.1992.156
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the synthetic retinoid etretinate on sputum cytology: results from a randomised trial

Abstract: Summary Laboratory studies, and one previous uncontrolled trial, have

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…Because bronchial metaplasia is reversible, it has been used as an intermediate endpoint for several lung cancer prevention trials, some of which have included various retinoids (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Because bronchial metaplasia is reversible, it has been used as an intermediate endpoint for several lung cancer prevention trials, some of which have included various retinoids (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…All three of the randomized trials of retinoids that have been conducted in smokers with metaplasia have been negative (see Table I). A placebo-controlled trial of 6 months of etretinate to reverse metaplasia in sputum samples [17] found that metaplasia was reversed in 32% of etretinate subjects and 30% of placebo subjects. A placebo-controlled trial of isotretinoin [18] for the reversal of metaplasia in bronchial biopsy specimens found that both study groups experienced a substantial reduction in metaplasia index (54% isotretinoin vs. 60% placebo).…”
Section: Lung Pre-malignancy Trialsmentioning
confidence: 97%
“…Reversal of these premalignant lesions through various treatment modalities may prevent progression to lung cancer. Studies have included various agents to treat sputum atypia [4][5][6][7] or bronchial squamous metaplasia [8][9][10][11]. One study even showed improvement of bronchial epithelium metaplasia in smokers with administration of folate and vitamin B 12 [12].…”
Section: Reversal Of Premalignant Lesionsmentioning
confidence: 99%